The Effect of Perception of Quality, Brand Communication and Brand Awareness on Somethinc Skincare Brand Loyalty - Riskiyansyah, Rahmad; Nuvriasari, Audita (LifeSciFi, 2024)
Skin care products (skincare) are an important need to maintain healthy skin. This research aims to analyze the influence of Perceived Quality, Brand Communication, and Brand Awareness on Somehinc Skincare Brand Loyalty. Using a sample of 100 users of Somethinc skin care products, this research used purposive sampling and questionnaires as data collection tools. Through multiple linear regression analysis and hypothesis testing, it was found that Perceived Quality and Brand Communication do not have a significant impact on brand loyalty. On the other hand, Brand Awareness has been identified as having a positive and significant influence on consumer loyalty. From the results of research and analysis regarding the Influence of Perceived Quality, Brand Communication, and Brand Awareness on Brand Loyalty of Somethinc Skincare Products, it can be concluded that Perceived Quality has no significant effect on Brand Loyalty of Somethinc Skincare Products. Brand Communication does not have a significant effect on Skincare Brand Loyalty. Brand Awareness has a positive and significant effect on Something's Skincare Brand Loyalty. This shows that Somethinc skincare products have unique qualities that can differentiate them from other skincare products so that consumers can easily remember Somethinc when buying skincare products.